Initial Growth of Eremanthus incanus (Less.) Less in Soil with Manganese - Araújo,Fillipe Vieira de (2018)
ABSTRACT The objective of this study was to evaluate the initial growth of Eremanthus incanus (Less.) Less (candeia) in soil with manganese doses. Additionally, it sought to assess manganese concentration, and accumulation in the organs of the plant as well as quantify the appropriate concentration of this element in the soil. The experiment was installed in a greenhouse and used manganese doses of 0, 50, 150 and 450 mg kg-1 soil. The experimental design used randomized blocks with five replications. Stem diameter and plant height; dry matter of root, shoot and total, and concentration and accumulation of manganese in the leaf, stem and root were evaluated. The manganese concentration in the soil was quantified using the Mehlich-1 and DTPA pH 7.3 extractors. A reduction in growth and high manganese concentrations in all parts of the plant were observed. For Melich-1 extraction the appropriate manganese concentration is 15.90 mg kg-1 and for DTPA it is 3.02 mg kg-1. The use of the candeia for phytoremediation is not recommended due to sensitivity to manganese.